Chinese herbal prescriptions for COVID-19 management: Special reference to Taiwan Chingguan Yihau (NRICM101) - Su, Yi-Chang; Huang, Guan-Jhong; Lin, Jaung-Geng (Frontiers in Pharmacology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a strain of coronavirus that causes COVID-19 (coronavirus disease 2019), the respiratory illness responsible for the ongoing COVID-19 pandemic. As at June 2022, increasing numbers of newly diagnosed COVID-19-associated pneumonia cases worldwide have attracted close attention from the international community. The present review analyzes and summarizes the treatment of COVID-19 with traditional Chinese medicine (TCM). A systematic analysis of the efficacies and benefits of TCM for the treatment of COVID-19 was performed, and the mechanisms underlying such treatment are summarized. This analysis of the literature highlights the potential of TCM to prevent and treat COVID-19 via antiviral, anti-inflammatory and immunomodulatory activities, with evidence showing that many TCM components act upon multiple targets and pathways. Famous TCM formulas include Qing-Fei-Pai-Du-Tang (QFPDT), Lianhuaqingwen Capsule (LHC), Taiwan Chingguan Yihau (NRICM101), and Jing Si herbal drink (JSHD). In particular, the botanical preparation NRICM101 was developed in 2020 for use in viral respiratory tract infections and is recommended for treating non-severe and mild COVID-19 infections. NRICM101 has been adopted for use in Taiwan for the clinical treatment of COVID-19. The common components and active ingredients of 10 TCM preparations have been analyzed for the most promising substances. This review aims to provide reliable evidence demonstrating the therapeutic efficacy of TCM substances in support of their further development against novel coronavirus infectious diseases in Taiwan.